Role of Training and Detraining on Inflammatory and Metabolic Profile in Infarcted Rats: Influences of Cardiovascular Autonomic Nervous System - Bruno Rodrigues; Aline Alves Santana; Aline Boveto Santamarina; Lila Missae Oyama; Érico Chagas Caperuto; Cláudio Teodoro de Souza; Catarina de Andrade Barboza; Leandro Yanase Rocha; Diego Figueroa; Cristiano Mostarda; Maria Cláudia Irigoyen; Fábio Santos Lira (Hindawi Limited, 2014)
The aim of this study was to evaluate the effects of exercise training (ET, 50-70% of VO2 max, 5 days/week) and detraining (DT) on inflammatory and metabolic profile after myocardial infarction (MI) in rats. Male Wistar rats were divided into control (C, n=8), sedentary infarcted (SI, n=9), trained infarcted (TI,  n=10; 3 months of ET), and detrained infarcted (DI, n=11; 2 months of ET + 1 month of DT). After ET and DT protocols, ventricular function and inflammation, cardiovascular autonomic modulation (spectral analysis), and adipose tissue inflammation and lipolytic pathway were evaluated. ET after MI improved cardiac and vascular autonomic modulation, and these benefits were correlated with reduced inflammatory cytokines on the heart and adipose tissue. These positive changes were sustained even after 1 month of detraining. No expressive changes were observed in oxidative stress and lipolytic pathway in experimental groups. In conclusion, our results strongly suggest that the autonomic improvement promoted by ET, and maintained even after the detraining period, was associated with reduced inflammatory profile in the left ventricle and adipose tissue of rats subjected to MI. These data encourage enhancing cardiovascular autonomic function as a therapeutic strategy for the treatment of inflammatory process triggered by MI.